L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

Why Lhasa de Sela Matters - Goodman, Fred (University of Texas Press, 2019)

« Cohérence d’une œuvre métissée » : extrait de thèse de doctorat (2007) - Makdissi-Warren, Katia (Circuit, 2019)

Katia Makdissi-Warren : étapes et œuvres marquantes - Pascal, Noémie (Circuit, 2019)

L’univers de Katia Makdissi-Warren (un diagramme) - Pascal, Noémie (Circuit, 2019)

Création contemporaine et partage des traditions : à la rencontre de Katia Makdissi-Warren - Tremblay, Vicky (Circuit : musiques contemporaines, 2019)
Un article de la revue Circuit, diffusée par la plateforme Érudit.